Pengaruh Penerapan Algoritma Pemrograman Pada Kurikulum Merdeka - Hartanti, Tri; Yahfizham (CV. ITTC INDONESIA, 2023)
Independent curriculum is an educational approach that gives students the freedom to choose and structure their learning according to their interests and needs. In this context, the impact of programming algorithms on the Merdeka curriculum is an interesting research topic. A programming algorithm is a structured set of steps or procedures for completing a task on a computer. The purpose of this study is to determine the impact of programming algorithms on the Merdeka curriculum and its impact on the development of students' computational and problem-solving skills. Research methods used are library research and content analysis. The findings show that applying programming algorithms to the Merdeka curriculum can bring significant benefits to students. Students learn to plan effective steps to solve a problem, divide it into small parts and organize the correct sequence of implementation. They also develop logical, analytical and creative thinking through pattern recognition, decision making and data manipulation. In addition, teaching programming algorithms in the Merdeka curriculum can help students develop broader problem-solving abilities. He learned to identify problems, design effective solutions, and test and refine the solutions. These skills can be applied in many contexts, not only in computer programming, but also in everyday life. Thus, the impact of programming algorithms on independent curriculum can make a valuable contribution to the development of students' numeracy and problem-solving skills. However, care must be taken to ensure that programming her algorithm education is guaranteed is adapted to the age and ability level of students and is presented in an interesting and interactive manner.